2023
DOI: 10.37945/cbr.2022.12.06
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Corporate Governance Mechanisms and Financial Institution Performance. A COVID-19 Perspective

Abstract: This article assesses the possibility of a relationship between corporate governance mechanisms and financial institutions performance in an emerging country such as Romania. The sample consists of 30 financial institutions and the data were collected manually from the annual reports. The size of the board, the size of the executive board, the diversity of the gender of the board, the duality of the CEO and the size of the audit committee were chosen as metrics for corporate governance, while ROA and ROE were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…We identify a negative and significant impact for ROA, whereas for ROE the impact is negative and insignificant. The results are in agreement with Carnini Pulino et al (2022) who also identified a negative impact of ENV scores on financial performance and El Khoury et al (2022) who identify a negative and insignificant impact of environmental score on ROE and Mititean and Sărmaș (2023) who found an insignificant impact of ENV score on ROE. Social performance negatively affects financial performance, Vol.11 (2023) no.4, pp.385-401;DOI 10.2478DOI 10.…”
Section: Discussion Of the Findingssupporting
confidence: 88%
“…We identify a negative and significant impact for ROA, whereas for ROE the impact is negative and insignificant. The results are in agreement with Carnini Pulino et al (2022) who also identified a negative impact of ENV scores on financial performance and El Khoury et al (2022) who identify a negative and insignificant impact of environmental score on ROE and Mititean and Sărmaș (2023) who found an insignificant impact of ENV score on ROE. Social performance negatively affects financial performance, Vol.11 (2023) no.4, pp.385-401;DOI 10.2478DOI 10.…”
Section: Discussion Of the Findingssupporting
confidence: 88%